2022
DOI: 10.5206/eei.v31i1.14097
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Parents of Children with Special Educational Needs: Self-Efficacy and School Supports During COVID-19

Abstract: The role of parents in supporting at-home learning increased dramatically in the spring of 2020. Schools in most Canadian provinces closed physically due to COVID-19, and remote-learning options were quickly developed to ensure continued education for students. Many students with special educational needs, who typically benefit from a range of supports from school, became reliant on parents to provide means of access to and participation in remote learning. Using an online survey, we explored the perceptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This result is not in line with the extant literature, which reports instead that parents of children with disability and SNs usually have lower levels of self-efficacy and satisfaction [ 46 , 47 , 48 ]. A study by Whitley, et al [ 49 ] found low levels of parental self-efficacy in parents of children with SNs. These parents were not satisfied with the academic support received from the school.…”
Section: Discussionmentioning
confidence: 99%
“…This result is not in line with the extant literature, which reports instead that parents of children with disability and SNs usually have lower levels of self-efficacy and satisfaction [ 46 , 47 , 48 ]. A study by Whitley, et al [ 49 ] found low levels of parental self-efficacy in parents of children with SNs. These parents were not satisfied with the academic support received from the school.…”
Section: Discussionmentioning
confidence: 99%